Analisis Yuridis Hukuman Pidana bagi Anak Pelaku Tindak Pidana Penyalahgunaan Narkotika Studi Putusan Nomor 3/Pid.Sus-Anak/2021/PN Bnt - Iwan Setyawan; Nita Octavia Kawi; Jelita Jelita (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the factors causing children to become involved in narcotics abuse, the judges’ considerations in delivering verdicts, and the conformity of such decisions with applicable legal provisions. This research employs a normative juridical method with a descriptive-analytical approach, based on literature review and analysis of Decision Number 3/Pid.Sus-Anak/2021/PN Bnt. The results indicate that children’s involvement in narcotics-related crimes is influenced by multidimensional factors, namely economic, environmental, and legal factors. Economic factors include family financial pressure; environmental factors involve peer influence and lack of parental supervision; while legal factors relate to limited understanding of legal consequences. Judges’ considerations in rendering decisions are not only based on juridical aspects but also take into account the social and psychological conditions of the child. However, the imposition of imprisonment is considered not fully aligned with the principles of restorative justice and child protection. Therefore, it is necessary to optimize the implementation of diversion and non-penal approaches in the juvenile justice system.